The Physical Condition of The Sukoharjo Pencak Silat Athlete in Team Category - Khotimah, Mutiara Nurul; Syaifullah, Rony; Hendarto, Singgih (Universitas Negeri Semarang, 2022)
Pencak silat is a sport related to physical needs and physical readiness to support the pencak silat movement. This study aims to determine the energy system in each stance, physical needs and to find out statistical data and the average physical need. This research is a descriptive quantitative with purposive sampling technique. Data were taken using the test items of Push Ups, Sit Ups, 300 M Run, Split Test, 20 M Sprint, Triple Jump, Shuttle Run, Ball Throw, Multi Fitnes-Stages. The research subjects were 6 people which were divided into 3 sons and 3 daughters. Data analysis used descriptive statistics. The results in the male sample showed perfect categories on the triple jump leg muscle power test and medicine ball throw arm muscle power test, very good on the push up arm muscle strength test, sit up abdominal muscle strength, anaerobic 300 m running test, side splits flexibility test, good category on the shuttle run agility test, above average category on Multi Fitnes- Stages, everage category on the 20 m sprint speed test. In the female sample, the results of the push-up arm strength test were in the very good category, the results of the sit-up abdominal muscle strength test were in the very good category, the results of the 300 m run test were in good and medium categories, the side splits test results were in good and medium categories, and the speed test results. 20 m sprint with less category, triple jump leg muscle power test results in good and sufficient category, shuttle run agility test results in sufficient category, medicine ball throw arm muscle power test results with perfect category, below average category endurance test results.